Multiplex gene analysis reveals T-cell and antibody-mediated rejection-specific upregulation of complement in renal transplants - Eva Vonbrunn (Nature Portfolio, 2021)
Abstract In renal transplantation, complement is involved in ischemia reperfusion injury, graft rejection and dysfunction. However, it is still unclear how induction of complement and its activation are initiated. Using allograft biopsies of a well-characterized cohort of 28 renal transplant patients with no rejection (Ctrl), delayed graft function (DGF), acute T-cell-mediated (TCMR) or antibody-mediated rejection (ABMR) we analyzed differences in complement reaction. For that mRNA was isolated from FFPE sections, quantified with a multiplex gene expression panel and correlated with transplant conditions and follow-up of patients. Additionally, inflammatory cells were quantified by multiplex immunohistochemistry. In allograft biopsies with TCMR and ABMR gene expression of C1QB was 2-4 fold elevated compared to Ctrl. In TCMR biopsies, mRNA counts of several complement-related genes including C1S, C3, CFB and complement regulators CFH, CR1 and SERPING1 were significantly increased compared to Ctrl. Interestingly, expression levels of about 75% of the analyzed complement related genes correlated with cold ischemia time (CIT) and markers of inflammation. In conclusion, this study suggest an important role of complement in transplant pathology which seems to be at least in part triggered by CIT. Multiplex mRNA analysis might be a useful method to refine diagnosis and explore new pathways involved in rejection.